A Bibliometric Method for Analysis of Systems Engineering Research. Issue 1 (30th September 2020) - Oosthuizen, Rudolph; Pretorius, Leon
Abstract: Since systems engineering is still a relatively young and growing discipline, it requires a periodic analysis, taking into account past research to derive the requirements for future growth. Published research provides a good indication on the progress and maturity of a scientific discipline. Bibliometric analysis is a valuable tool to assess published research. This paper establishes a method to determine the main research topics published in the Systems Engineering Journal (INCOSE) since its inception. The research and associated analysis method applies Natural Language Processing with Topic Modelling to extract the main topics from the abstracts of all the papers published in the journal. The analyzed data provides the trends in topic coverage over time.